2016
DOI: 10.1002/erv.2454
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis on Resting State High‐frequency Heart Rate Variability in Bulimia Nervosa

Abstract: Findings suggest higher vagal activity in BN at rest, particularly in unmedicated samples with lower body mass index. Potential mechanisms underlying these findings and implications for routine clinical care are discussed. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
(118 reference statements)
3
23
1
1
Order By: Relevance
“…It would be interesting to use both the central and autonomic measure to investigate the arousal dysfunction of depression and anxiety in a future study. It would also be important to apply the present HRV paradigm to other psychiatric disorders, including schizophrenia, bipolar disorder, and eating disorder, to verify the specificity of the findings …”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to use both the central and autonomic measure to investigate the arousal dysfunction of depression and anxiety in a future study. It would also be important to apply the present HRV paradigm to other psychiatric disorders, including schizophrenia, bipolar disorder, and eating disorder, to verify the specificity of the findings …”
Section: Discussionmentioning
confidence: 99%
“…Finally, EDs have been associated with alterations in the autonomic nervous system (Mazurak et al, 2011; Peschel et al, 2016a,b). In this regard, we found no significant in-task HRV differences when conducting the Playmancer-ER task.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that both higher and lower HRV are mainly determined by the parasympathetic system (Malik et al, 1996; Houle and Billman, 1999; Goldstein et al, 2011; Reyes del Paso et al, 2013; Ramírez et al, 2015). EDs have been associated with alterations in the autonomic nervous system, however, results are still inconclusive with most studies accounting increased HRV to parasympathetic nervous system dominance, whereas others describe decreased HRV conveying dominance of the sympathetic nervous system, or no differences comparing HRV in ED patients to controls (Mazurak et al, 2011; Peschel et al, 2016a,b). Additionally, HRV is an objective measure that has been considered as an index of ER capacity in a large number of studies (Di Simplicio et al, 2012; Thayer et al, 2012; Tuck et al, 2016; Visted et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3.3 | Autonomic functioning 3.3.1 | Relevance of heart rate variability in EDs Altered autonomic nervous system functioning has been the focus of a substantial body of research in the ED field, particularly heart rate variability (for reviews see Mazurak, Enck, Muth, Teufel, & Zipfel, 2011;Peschel et al, 2016). Heart rate variability involves a complex interplay between the sympathetic and parasympathetic branches of the autonomic nervous system.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…High levels of heart rate variability are generally associated with high levels of social engagement and adaptive self-regulation (Geisler et al, 2013) whereas low levels of heart rate variability have been shown to be associated with a wide range of psychopathology and deficits in cognitive control (Hovland et al, 2012;Kemp, Quintana, Quinn, Hopkinson, & Harris, 2014;Santerre & Allen, 2007). Recent reviews in EDs suggest that bulimia nervosa is characterized by heightened levels of resting state heart rate variability and impaired stress response to stress-related cues (Peschel et al, 2016), and anorexia nervosa is associated with a range of disturbances in autonomic nervous system functioning, including imbalances between the parasympathetic nervous system and sympathetic nervous system (Mazurak et al, 2011). However, there has been a great deal of heterogeneity in methods and the pattern of results across studies.…”
Section: Assessment Methodologymentioning
confidence: 99%